Aditivos na alimentação de frangos de corte: desempenho, características morfométricas e funcionais - Alva, Juan Carlos Ríos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Acidifiers and probiotics are considered alternative feed additives (FA) for growth promotant antibiotics, and these FA have been shown to improve broiler performance and affect gut morphometrics. Two experiments were conducted to evaluate the effects of the dietary addition of two probiotics (Paenibacillus sp. and Bacillus subtilis) and citric acid on broiler performance, intestinal, pancreatic and hepatic morphometrics and pancreatic enzyme activity. For both experiments, four hundred d-old male Ross 308 chicks were placed in 20 floor pens with reused litter and fed common corn-soybean basal diets (BD) that contained salinomycin. The five dietary treatments utilized in the first experiment resulted from using the BD without feed additives (WFA) as a negative control, adding a growth promotant antibiotic (lincomycin) as a positive control, and adding Paenibacillus sp. at 30, 45 and 60 ppm. The same positive and negative controls were used in the second experiment with three other dietary treatments resulting from the addition of citric acid, Paenibacillus sp. and Bacillus subtilis (GalliPro®) to the BD. In both experiments, BW, feed intake (FI) and FCR corrected for mortality were evaluated at the starter (1-21d), grower (22-35d) and finisher (36-42d) phases and the whole grow out. At 14, 28 and 42d intestinal samples of one chicken per pen were collected to evaluate villi height, density and width and goblet cells in the duodenum, jejunum and ileum. At 28 and 42d of age, pancreatic amylase, trypsin and chymotrypsin activities were evaluated. In the first experiment, data were analyzed in a CRD with regression analyses of Paenibacillus sp. levels and orthogonal contrasts with positive and negative controls. Data in the second experiment were analyzed in a CRD with orthogonal contrasts against the positive control. In the first experiment, no significant effects (P>0.05) of Paenibacillus sp. inclusion levels were observed on ...

Ácidos orgânicos e probióticos são considerados aditivos alternativos aos antibióticos promotores de crescimento (APC), e têm demonstrado contribuir no desempenho das aves e ter efeito positivo na morfometria do intestino. Dois experimentos foram conduzidos para avaliar o efeito da adição de dois probióticos (Paenibacillus sp. e Bacillus subtilis) e ácido cítrico no desempenho, morfometria intestinal, hepática e pancreática e atividade de enzimas pancreáticas. Para os dois experimentos, foram utilizados 400 pintinhos machos Ross 308 distribuídos em 20 boxes com cama reutilizada e alimentados com dieta à base de milho e farelo de soja (DB) contendo salinomicina. Os cinco tratamentos utilizados no primeiro experimento foram, dieta basal sem aditivos (DB) como controle negativo, dieta DB com lincomicina como controle positivo e dietas com 30, 45 e 60 ppm do probiótico Paenibacillus sp. Os mesmos controles positivo e negativo utilizados no primeiro experimento foram usados no segundo experimento com três outros tratamentos como resultado da adição de ácido cítrico, Paenibacillus sp. e Bacillus subtilis (GalliPro®). Em ambos experimentos, ganho de peso (GP), consumo de ração (CR), e conversão alimentar (CA) foram avaliados durante a fase inicial (1-21 d), crescimento (22 a 35 d), e final (36 a 42 d) e durante todo fase de criação (1 a 42 d e 1 a 49 d). Aos 14, 28 e 42 dias, amostra de intestino de uma ave por box foi coletada para avaliar o comprimento, largura e densidade das vilosidades e número de células caliciformes do duodeno, jejuno e íleo, assim como o número das células de Kupffer do fígado, ácinos serosos e ilhotas pancreáticas. Aos 28 e 42 dias de idade foram avaliadas a atividade da amilase, tripsina e quimotripsina do pâncreas. No primeiro experimento, os dados foram analisados em um delineamento inteiramente casualizado (DIC) com análise de regressão dos níveis do probiótico ...
Keywords: Frango de corte - Nutrição; Ácidos orgânicos; Antibioticos; Enzimas; Probióticos; Suplementos dieteticos; Probiotics